Étude par absorptiométrie de la densité minérale osseuse dans une population médiévale (nécropole de Notre Dame du Bourg, Digne, Alpes de Haute-Provence France, XIe-XIIIe et XVIe-XVIIIe s.) - Jean Fulpin; Bertrand Mafart; Pierre-Yves Chouc; Gabrielle Demians d'Archimbaud (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The purpose of the study was to determine post-menopausal bone mineral content in women living in a semi-rural region at two different archaeological periods, i.e. Medieval 11th century and pre-modern 17th century. The femurs of 18 women under the age of 30 years at death and 40 women over the age of 60 at death were collected from the Notre Dame du Bourg Necropolis in Digne, Alpes-de-Haute-Provence, France. Measurements of the neck and Ward’s triangle regions were made by dual-energy X-ray absorptiometry after documenting the absence of radiologically detectable disease and of variations between two measurements and between right and left sides. Comparison of findings showed a decrease in bone mineral content between the two age groups (under 30 vs. over 60) in both the medieval and pre-modern population. Bone mineral content was comparable to that observed in the populations of present-day industrial nations. The extent of loss in some specimens were suggestive of osteoporosis.